Penggambaran Perempuan Muslimah dalam Film Sisterlillah - Pipit Susilawati; Dyah Kusumawati (UNIVERSITAS KALBIS, 2022)
The depiction of the figure of a Muslim woman, namely a Muslim woman who behaves in daily life following the teachings of Islam. The purpose of this study was to determine the depiction of Muslim women in the film Sisterlillah. In this study, the researcher uses the theory of social reality construction in mass media, constructivism paradigm, qualitative research approach, descriptive research type and content analysis research method using Charles Sanders Peirce's semiotics (sign, object, interpretant). The results of the study show that the figure depicting Muslim women in the film is depicted through five female Muslim characters who are energetic, highly educated, have careers, prioritize marriage and stay away from adultery.